Nitrosative stress by peroxynitrite impairs ATP production in human spermatozoa. (2nd May 2016) - Uribe, P.; Treulen, F.; Boguen, R.; Sánchez, R.; Villegas, J. V.
Summary: The most toxic species in live systems include reactive nitrogen species such as peroxynitrite, which at high levels induces nitrosative stress. In human spermatozoa, the negative effect of peroxynitrite on motility and mitochondrial membrane potential was recently demonstrated, and the hypothesis of this work is that impairment of ATP production could be one cause of the effect on motility. Therefore, the aim here was to evaluate ATP production by both glycolysis and oxidative phosphorylation (OXPHOS) in spermatozoa exposed to peroxynitrite in vitro . Human spermatozoa were incubated with SIN‐1, a molecule which generates peroxynitrite, and the ATP level was evaluated. Then, to inactivate glycolysis or OXPHOS, spermatozoa were incubated with pharmacological inhibitors of these pathways. Spermatozoa treated for inactivating one or the other pathway were exposed to SIN‐1, and the ATP level was compared to the control without SIN‐1 in each condition. The ATP level fell after peroxynitrite exposure. The ATP in spermatozoa treated for inactivating one or the other metabolic pathway and subsequently exposed to peroxynitrite was reduced compared with the control. These results show for the first time that an important mechanism by which peroxynitrite reduces sperm function is the inhibition of ATP production, affecting both glycolysis and OXPHOS.